Pengaruh Kompetensi Pegawai Dan Pelatihan Terhadap Kualitas Layanan Dinas Perpustakaan Dan Arsip Daerah Kota Bima - Jihan Fahiran; Firmansyah Kusumayadi (UNIVERSITAS MARITIM AMNI SEMARANG, 2023)
The success of an organization such as a library is greatly influenced by the human resources available in the library. The human resources contained in it are employees, where employees have a very important role in helping to achieve the goals or targets desired by the library and can help in building a positive image of the community. The role of an employee in helping develop a library can be carried out well if the library has quality employees, which can be seen from the good or bad quality of the services they provide. Kurniawan (Indarwati, 2020) states that